Combined effects of raw materials and solvent systems on the preparation and properties of regenerated cellulose fibers. (5th September 2015) - Chen, Jinghuan; Guan, Ying; Wang, Kun; Zhang, Xueming; Xu, Feng; Sun, Runcang
Highlights: The combined effect of materials and solvents on fibers was investigated in detail. Cellulose dissolution was mainly determined by the dissolvability of solvents. Dissolution time was influenced by the properties of raw materials. The strength of fibers was directly proportional to raw materials' molecular weight. For the same material, the fibers' strength was varied with the type of solvents. Abstract: To investigate the combined effects of materials and solvents on the preparation, structural and mechanical properties of regenerated cellulose fibers, four cellulosic materials (microcrystalline cellulose, cotton linter pulp, bamboo pulp and bleached softwood sulfite dissolving pulp) and six non-derivative solvents (NaOH/urea aqueous solution, N, N -dimethylacetamide/lithium chloride, N -methyl-morpholine- N -oxide, 1-butyl-3-methylimidazolium chloride, 1-allyl-3-methylimidazolium chloride and 1-ethyl-3-methylimidazolium acetate) were used to prepare fibers with wet spinning method. The results showed that the dissolvability of solvent was the determining factor in cellulose dissolution, and the dissolving time was influenced by the raw materials' properties, such as molecular weight, exposed area and hemicellulose content. The crystallinity and elongation at break of the fibers were almost fixed and not affected by the materials and solvents. However, the tensile strength of the fibers was directly proportional to the molecular weight of the raw materials, and varied with the type of solvents through cellulose degradation.